Anthocyanins isolated from blueberry ameliorates CCl4 induced liver fibrosis by modulation of oxidative stress, inflammation and stellate cell activation in mice. (October 2018) - Sun, Jianchao; Wu, Yafeng; Long, Cuizhen; He, Ping; Gu, Junying; Yang, Lei; Liang, Yaodong; Wang, Yuping
Abstract: To study the mechanism of anthocyanins from blueberry on mice model of hepatic fibrosis. We observed that the levels of serum ALT and AST of 100 mg*kg-1*d-1, 200 mg*kg-1*d-1 anthocyanins group were reduced compared to the CCl4 treated group. Mitochondrial electron chain complex 1 and 2 activities, determined by microplate assays, were reduced in CCl4 treated group and restored by anthocyanin treatment. MDA and protein carbonyl content of liver homogenate were induced by CCl4 and anthocyanin treated group reduced both significantly.Monocyte chemoattractant protein 1 (MCP1), Interleukin 1 beta (IL1β), macrophage inflammatory protein 2 (MIP-2) were induced by CCl4 were attenuated by anthocyanin. Colagen Ⅲ and α-SMA was significantly increased as determined by histology and anthocyanins decreased their level. The protein levels of MMP-9, TIMP1 and PCNA of liver homogenate was also modulated by anthocyanins. In isolated hepatic stellate cells, activation as determined by fibrotic gene expression was attenuated by anthocyanin. Anthocyanins from blueberry may have protective effects on CCl4 induced hepatic fibrosis. The mechanism may be related to reduce ROS generating sources and associated oxidative damage, decrease the influence of pro-inflammatory cytokines, and suppress the activity of hepatic stellate cells and downregulation TIMP1, PCNA, Col-Ⅲ, α-SMA and up-regulation MMP-9.